Manajemen Pendidikan untuk Pondok Pesantren - Badrudin, Badrudin; Ardiansyah, Ardiansyah; Sahal, Eska Hifdiyah (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
The ideal manager for the kiai leading the Islamic boarding school and his companions or the first person is a visionary person. Islamic boarding schools led by visionary people will be enlightened and motivated to make clear plans and goals for the future of the Islamic boarding school and its students. One example is the idea of the best Islamic education system in the world, namely Islamic boarding schools with madrasas which are more ideal. Apart from that, follow the usual procedures or rules at Islamic boarding schools. The culture of being very obedient to kiai, who have enormous authority in Islamic boarding schools, is one of the factors that drives this. Moreover, it relies on the “management system” of thousands of Islamic boarding schools, each of which has a different level of culture of obedience to kiai. In the education system, each Islamic boarding school has different “styles”.